1998
DOI: 10.1116/1.580953
|View full text |Cite
|
Sign up to set email alerts
|

Surface morphology of ex situ sulfur-passivated (1×1) and (2×1) InP(100) surfaces

Abstract: Ex-situ aqueous ͑NH 4 ) 2 S treated sulfur-passivated InP substrates have been studied using ultrahigh vacuum scanning tunnelling microscopy ͑STM͒ and low-energy electron diffraction ͑LEED͒. The morphology of the passivated surface was imaged after a mild sample annealing. The STM images of a surface exhibiting a good 1ϫ1 LEED pattern show that the top layer of the sulfur-passivated surface is poorly ordered. A surface bilayer atomic step has been observed to be common on sulfur-passivated surfaces. The magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In this case, the diffraction pattern will not reflect the presence of the disordered top atomic layer that is observed in the STM images since the contribution of the surface adsorbates is insufficient to influence the electron diffraction pattern. Similar findings have also been reported in literature for (NH 4 ) 2 S treated InP substrates 31 as well as for in situ prepared S/Ge substrates. 32 Our results clearly indicate the strength and need of using complementary surface analysis techniques such as STM and LEED to provide detailed information about complex surface atomic structures.…”
Section: Resultssupporting
confidence: 91%
“…In this case, the diffraction pattern will not reflect the presence of the disordered top atomic layer that is observed in the STM images since the contribution of the surface adsorbates is insufficient to influence the electron diffraction pattern. Similar findings have also been reported in literature for (NH 4 ) 2 S treated InP substrates 31 as well as for in situ prepared S/Ge substrates. 32 Our results clearly indicate the strength and need of using complementary surface analysis techniques such as STM and LEED to provide detailed information about complex surface atomic structures.…”
Section: Resultssupporting
confidence: 91%
“…Similar to that observed from a sample treated by a wet passivation process, a 1 × 1 LEED pattern is observed after the surface is heated to 500 K. ,,, However, in contrast with the result obtained from a previous study of wet passivation, a change of LEED pattern from (1 × 1) to (2 × 1) is not observed when the surface is further annealed to 540 K . On the basis of a recent STM study, it was found that the top layer of the S-passivated surface lacks a long-range order, and the (1 × 1) LEED pattern was postulated to originate from the underlayer substrate . However, if the (1 × 1) surface order is imposed, the bridge site is proposed to provide the most favorable energy for the S absorption, as proposed in the case of GaAs−S. , In the previous XPD studies, the S atoms on the InP(100) by wet passivation were also proposed to bridge-bond to two In atoms of the first layer, which have two dangling bonds in opposite directions. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The presence of surface states arising from atomic steps has also been confirmed by scanning tunneling microscopy on the S-passivated InP͑100͒ surface. 50 Even after S-passivation the surface state density still remains high at ϳ10 12 cm −2 / eV. 51 More compelling is the high density of surface states at 1.2-1.3 eV above the VBM reported for a variety of different chemically treated InP surfaces.…”
Section: B Injection From Surface Statesmentioning
confidence: 99%